Brain Korea 21 Phase II A New Evaluation Model - Seong, Somi (RAND Corporation, 2008)
The Brain Korea 21 Program (BK21), which seeks to make Korean research universities globally competitive and to produce more high-quality researchers in Korea, provides funding to graduate students and professors who belong to research groups at top universities. The authors develop quantitative and qualitative models to evaluate how well BK21 is fulfilling its goals and make suggestions for further stimulating Korean university research.